Rancang Bangun IOT Cloud Platform Berbasis Protokol Komunikasi MQTT - Moh Wildan Habibi; Adhitya Bhawiyuga; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Internet of Things (IoT) referring to a network that linking various device in the physical world with a variety of different protocols. However, there are limitations in terms of computing and storage because IoT device only use minimum computational and storage components. While cloud is a virtual environment that generally has a big capacity of computing and storage. By integrating cloud and IoT, it is necessary to divert IoT device's computational process and storage towards cloud, so that cloud can resolve the limitations on the IoT device. There are two main issues in the integration, heterogeneity and security. Heterogeneity refers to number range of devices that can communicate with the cloud, so it is necessary to use specific communication protocol so that all devices can be connected to the cloud. Security refers to the validity of the IoT devices that can transmit data to the cloud. From the previous explanation, then this research makes an architecture of IoT cloud platform that use MQTT communication protocol to resolve the problem of heterogeneity. Whereas to ensure the validity of IoT devices that can transmit data, constructed a mechanism to manage IoT device, authentication, and authorization. The performance test results showed, built systems capable of handling the publisher up to 250 publishers in each second.